Strategi Pembelajaran Inovatif dalam Meningkatkan Kreativitas Siswa Sekolah Dasar - Rohana Silaen; Mutiara Lestari Aritonang; Feni Fantikasari Hasugian; Hendry Meiman Lahagu; Melly A. Br.Sihombing (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Creativity is an important ability that needs to be developed from an early age. At the elementary school level, implementing innovative learning strategies can be the key to fostering student creativity. This article examines various innovative learning strategies that are effective in increasing elementary school students' creativity. Through project-based, discovery, cooperative, technology, and STEAM approaches, students are expected to develop creative thinking skills that will benefit them in the future.